John Sherman Cooper : the global Kentuckian - Schulman, Robert, 1916-2008 (Kentucky Bicentennial bookshelf., 2004)
From the late 1940s through the 1970s, John Sherman Cooper, a quiet lawyer from Kentucky, ascended to become one of America's leading statesmen. Cooper's embodiment of the values of his rural upbringing, his understanding of people and their problems, and his openness and integrity were the qualities that Schulman believes, paradoxically won him success in dealing with the most powerful and sophisticated of the world's leaders. They are the qualities elicited in this warm memoir. Cooper's political career began in his native Pulaski County, where he served two terms as county judge during the D.